Effects of MICs and sub-MICs of antibiotics on production of capsular polysaccharide of Klebsiella pneumoniae. - Held, T K (1995)
In the present study, we examined whether MICs and sub-MICs of antimicrobial agents belonging to two different classes, ciprofloxacin and ceftazidime, were able to influence the production and release of cell-associated and soluble (extracellular) capsular polysaccharide (CPS), respectively, in a heavily encapsulated strain of Klebsiella pneumoniae (B5055). Using a CPS-specific enzyme-linked immunosorbent assay, we found that the amount of cell-associated CPS increased in a dose-dependent manner by more than 10-fold under the influence of the MIC of ceftazidime and by more than 100-fold under the influence of the MIC of ciprofloxacin. The largest amounts of CPS were measured by using the MIC of either antibiotic substance. Electron microscopic studies showed that the diameter of the capsule was significantly increased compared with the diameter for untreated controls. Thus, both antimicrobial agents genuinely stimulated CPS production.